High-voltage-resistant electrolyte and sodium ion battery containing same
By using sulfonate esters and sulfone cosolvents in sodium ion batteries to form a stable cathode electrolyte interface film, the problem of poor cycling performance of sodium ion batteries at high voltage is solved, and higher battery stability and longer The service life of the product is reduced while reducing costs.
Patent Information
- Application Number
- CN202411175195.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-13
AI Technical Summary
Existing sodium ion batteries have poor circulation performance under high voltages, and the electrolyte is prone to decomposition, resulting in unstable cathode interface and damage to the positive electrode structure, affecting the cycle stability and safety of the battery.
A high-voltage resistant electrolyte is adopted, including carbonate co-solvent, electrolyte sodium salt, carbonate electrolyte additive and high-voltage co-solvent. The high-voltage co-solvent is a sulfonate and/or sulfone co-solvent, through these components A strong and stable cathode electrolyte interface (CEI) film is formed under high pressure, reducing interface impedance and protecting the cathode material.
It improves the cycling performance and stability of sodium ion batteries at high voltages, extends the battery life, reduces costs, and reduces the use of fluorocarbonates.
Smart Images

Figure CN119133610A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a high-voltage resistant electrolyte and a sodium ion battery containing the same. Background Art
[0002] Sodium-ion batteries (SIBs) have many advantages, such as low cost, high safety, and energy storage principles similar to lithium-ion batteries. However, the development of their high energy density still faces great challenges. The cathode material has a profound impact on the energy density of the battery. Among them, layered transition metal oxides (NaxTMO2, TM = transition metal, x≤1) have become one of the most promising cathode materials due to their high capacity, easy synthesis, and abundant elemental resources. In order to obtain higher capacity, increasing the cut-off voltage is an effective means. However, the electrolyte of existing commercial batteries is difficult to stabilize under high voltage and cannot match the high-voltage cathode. Therefore, the development of an advanced electrolyte that is compatible with the high-voltage cathode and can achieve stable cycling is crucial to achieving high-energy-density SIBs.
[0003] At present, carbonate electrolytes are the most widely used electrolyte system in sodium ion batteries. However, this type of electrolyte is prone to decomposition under long-term high-voltage cycles, resulting in an unstable cathode electrolyte interface (CEI). At the same time, under high-voltage conditions, the destruction of the cathode structure may also lead to the dissolution of transition metals, thereby affecting the cycle stability of sodium ion batteries. The main solutions are to increase the salt concentration and use high-voltage additives. High-concentration electrolytes inhibit the oxidative decomposition of electrolytes under high voltages by increasing the number of complexes between sodium ions and solvent molecules, thereby improving the stability and safety of the battery. However, an increase in concentration will lead to a decrease in conductivity, resulting in an increase in the impedance of sodium ions during transmission in the electrolyte and at the interface, and a deterioration in the cycle performance and rate performance. High-voltage additives and new fluorinated solvents are committed to constructing an interface rich in NaF inorganics. However, fluorinated additives or solvents have low cost and poor salt dissolving ability, and are prone to produce corrosive HF byproducts that damage the cathode interface, leading to the dissolution of transition metals, rapid decline in battery performance, and poor cycle performance.
[0004] Therefore, it is necessary to propose a new high-voltage resistant electrolyte to improve the cycle performance of sodium ion batteries. Summary of the invention
[0005] In view of this, the present application provides a high-voltage resistant electrolyte and a sodium ion battery containing the same, which are used to solve the problem of how to improve the cycle performance of sodium ion batteries under high voltage.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a high-voltage resistant electrolyte, comprising a carbonate co-solvent, an electrolyte sodium salt, a carbonate electrolyte additive and a high-voltage resistant co-solvent, wherein the high-voltage resistant co-solvent is a sulfonate co-solvent and / or a sulfone co-solvent.
[0007] Preferably, the sulfonate co-solvent includes at least one of ethyl methanesulfonate, ethyl benzenesulfonate, and ethyl p-toluenesulfonate.
[0008] Preferably, the sulfone co-solvent includes at least one of sulfolane and ethyl methyl sulfone.
[0009] Preferably, the carbonate electrolyte additive includes at least one of fluoroethylene carbonate, difluoroethylene carbonate, and vinylene carbonate.
[0010] Preferably, the carbonate co-solvent includes at least one of ethylene carbonate and propylene carbonate; the electrolyte sodium salt includes at least one of sodium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate and sodium bis(fluorosulfonyl)imide.
[0011] Preferably, the volume ratio of the high pressure resistant co-solvent to the carbonate co-solvent is (25-80):(20-75).
[0012] Preferably, the carbonate electrolyte additive accounts for 1-5% of the total volume of the high-voltage co-solvent and the carbonate co-solvent.
[0013] Preferably, the concentration of the electrolyte sodium salt in the high-voltage electrolyte is 0.8-2 mol / L.
[0014] In a second aspect, the present application provides a sodium ion battery, which includes a high-voltage resistant electrolyte, a layered oxide positive electrode material, a negative electrode material and a separator.
[0015] Preferably, the layered oxide positive electrode material is Na 0.67 Mn 0.8 Cu 0.2 O2.
[0016] In a third aspect, the present application provides an application of a sodium ion battery at 2-4.5V.
[0017] The beneficial effects of this application are as follows: The electrolyte of the present application uses carbonate, sulfonate and / or sulfone high dielectric constant solvents as the main components of the electrolyte, and electrolyte sodium salt and carbonate electrolyte additives as the main auxiliary components. It has the characteristics of low viscosity, low flammability and high voltage resistance, which not only meets the requirements of sodium ion batteries for the high voltage resistance of electrolytes, but also ensures that sodium ion batteries have good cycle stability; The sodium ion battery of the present application adopts layered oxide as the positive electrode material. At the same time, the electrolyte of the present application contains sulfonate co-solvent and / or sulfone co-solvent, which can first oxidize and decompose on the surface of the layered oxide positive electrode material to form a strong, stable, thin and uniform CEI film, which is beneficial to further prevent the oxidative decomposition and consumption of carbonate co-solvent, reduce the interface impedance between the components in the battery, and realize efficient charge transfer and ion transport in the sodium ion battery; and the CEI film with a dense structure is beneficial to inhibit the dissolution of transition metal ions of the layered oxide positive electrode material, protect the structure of the positive electrode material from damage, and thus improve the cycle performance of the sodium ion battery using the layered oxide as the positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A comparison chart of cycle performance tests of batteries assembled with the electrolytes of Example 1 and Comparative Example 1; Figure 2 This is an ICP test result diagram of the battery assembled with the electrolyte of Example 1 and Comparative Example 1 after 400 cycles; Figure 3 This is a scanning electron microscope image of the positive electrode sheet of a battery assembled with the electrolyte of Example 1 after 400 cycles; Figure 4 This is a scanning electron microscope image of the positive electrode sheet of the battery assembled using the electrolyte of Comparative Example 1 after 400 cycles. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0020] The present application provides a high-voltage resistant electrolyte, comprising a carbonate co-solvent, an electrolyte sodium salt, a carbonate electrolyte additive and a high-voltage resistant co-solvent, wherein the high-voltage resistant co-solvent is a sulfonate co-solvent and / or a sulfone co-solvent.
[0021] The present application forms a stable CEI (cathode electrolyte interphase) film on the surface of the positive electrode material by preferentially oxidizing and decomposing sulfonate and / or sulfone co-solvents under high pressure. The CEI film is strong and dense, rich in Na2SO4, and prevents the oxidative decomposition and consumption of carbonate co-solvents, which is beneficial to reducing the impedance of sodium ions moving between the electrolyte and the lattice of the positive electrode material during charging and discharging; and the CEI film can effectively inhibit the dissolution of transition metal ions, protect the positive electrode material from damage, and thus help improve the cycle performance of sodium ion batteries at a high voltage of 2-4.5V.
[0022] On the other hand, since the high-voltage co-solvent of the present application has the ability to form a high-voltage CEI film, the amount of carbonate electrolyte additives used can be reduced. In particular, the sulfonate co-solvent has a more obvious effect in reducing the amount of fluorocarbonate used, thereby reducing costs.
[0023] In the present application, the preparation method of the high-voltage electrolyte is to mix the high-voltage co-solvent and the carbonate co-solvent, add the carbonate electrolyte additive, and then add the sodium salt and adjust the concentration to obtain the electrolyte.
[0024] In some embodiments, the sulfonate co-solvent includes at least one of ethyl methanesulfonate, ethyl benzenesulfonate, and ethyl p-toluenesulfonate.
[0025] In some embodiments, the sulfone co-solvent includes at least one of sulfolane and ethyl methyl sulfone.
[0026] Sulfonate or sulfone co-solvents are selected from the above substances, which can form a stable, strong and dense CEI film rich in Na2SO4 on the surface of the positive electrode material, which is beneficial to further prevent the oxidative decomposition and consumption of carbonate co-solvents, and can effectively inhibit the dissolution of transition metal ions, protect the positive electrode material from damage, and thus improve the use of layered oxides (such as Na 0.67 Mn 0.8 Cu 0.2 Cycling performance of sodium-ion batteries with O2 as cathode material at high voltage.
[0027] The carbonate co-solvent of the present application is a cyclic carbonate co-solvent; the carbonate electrolyte additive includes at least one of fluoroethylene carbonate, difluoroethylene carbonate, and vinylene carbonate.
[0028] In some embodiments, the carbonate co-solvent includes at least one of ethylene carbonate and propylene carbonate; and the electrolyte sodium salt includes at least one of sodium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate and sodium bis(fluorosulfonyl)imide.
[0029] In some embodiments, the volume ratio of the high-pressure co-solvent to the carbonate co-solvent is (25-80): (20-75), including but not limited to 25:35, 25:50, 25:70, 50:50, 50:30, 50:75, 70:30, 70:50, 70:75. Under the limited ratio of the high-pressure co-solvent and the carbonate co-solvent in the present application, it is beneficial to further improve the cycle performance of the sodium ion battery using layered oxides as the positive electrode material, and the layered oxides include but are not limited to Na 0.67 Mn 0.8 Cu 0.2 O2.
[0030] In some embodiments, the carbonate electrolyte additive accounts for 1-5% of the total volume of the high voltage co-solvent and the carbonate co-solvent.
[0031] In some embodiments, the concentration of the electrolyte sodium salt in the high-voltage electrolyte is 0.8-2 mol / L; the sodium salt at the above concentration is conducive to further improving the use of layered oxides (such as Na 0.67 Mn 0.8 Cu 0.2 O2) as the cycling performance of the positive electrode material.
[0032] The present application provides a sodium ion battery, which includes a high-voltage electrolyte, a layered oxide positive electrode material, a negative electrode material and a separator.
[0033] In some embodiments, the layered oxide cathode material is Na 0.67 Mn 0.8 Cu 0.2 O2.
[0034] The present application provides an application of a sodium ion battery at 2-4.5V.
[0035] The present solution is further described below through specific embodiments.
[0036] Example 1 A high-voltage resistant electrolyte comprises a carbonate co-solvent, an electrolyte sodium salt, a carbonate electrolyte additive and a high-voltage resistant co-solvent; the carbonate co-solvent is propylene carbonate, the electrolyte sodium salt is sodium hexafluorophosphate (NaPF6), the carbonate electrolyte additive is fluoroethylene carbonate, and the high-voltage resistant co-solvent is ethyl methanesulfonate; wherein the volume ratio of the high-voltage resistant co-solvent to the carbonate co-solvent is 30:70, the carbonate electrolyte additive accounts for 1% of the total volume of the high-voltage resistant co-solvent and the carbonate co-solvent, and the concentration of the electrolyte sodium salt is 1 mol / L.
[0037] The preparation method of the high-voltage electrolyte is as follows: ethyl methanesulfonate and propylene carbonate are mixed in a molar ratio, fluoroethylene carbonate is added, sodium hexafluorophosphate is added and the concentration is adjusted, and the electrolyte is obtained after being stirred evenly.
[0038] Example 2 A high-voltage resistant electrolyte comprises a carbonate co-solvent, an electrolyte sodium salt, a carbonate electrolyte additive and a high-voltage resistant co-solvent; the carbonate co-solvent is propylene carbonate, the electrolyte sodium salt is sodium hexafluorophosphate (NaPF6), the carbonate electrolyte additive is fluoroethylene carbonate, and the high-voltage resistant co-solvent is ethyl methanesulfonate; wherein the volume ratio of the high-voltage resistant co-solvent to the carbonate co-solvent is 50:50, the carbonate electrolyte additive accounts for 1% of the total volume of the high-voltage resistant co-solvent and the carbonate co-solvent, and the concentration of the electrolyte sodium salt is 2 mol / L.
[0039] The preparation method of the high-voltage electrolyte is as follows: ethyl methanesulfonate and propylene carbonate are mixed in a molar ratio, fluoroethylene carbonate is added, sodium hexafluorophosphate is added and the concentration is adjusted, and the electrolyte is obtained after being stirred evenly.
[0040] Example 3 A high-voltage resistant electrolyte comprises a carbonate co-solvent, an electrolyte sodium salt, a carbonate electrolyte additive and a high-voltage resistant co-solvent; the carbonate co-solvent is propylene carbonate, the electrolyte sodium salt is sodium hexafluorophosphate (NaPF6), the carbonate electrolyte additive is fluoroethylene carbonate, and the high-voltage resistant co-solvent is cyclopentane sulfone; wherein the volume ratio of the high-voltage resistant co-solvent to the carbonate co-solvent is 70:30, the carbonate electrolyte additive accounts for 1% of the total volume of the high-voltage resistant co-solvent and the carbonate co-solvent, and the concentration of the electrolyte sodium salt is 1 mol / L.
[0041] The preparation method of the high-voltage electrolyte is as follows: ethyl methanesulfonate and propylene carbonate are mixed in a molar ratio, fluoroethylene carbonate is added, sodium hexafluorophosphate is added and the concentration is adjusted, and the electrolyte is obtained after being stirred evenly.
[0042] Example 4 A high-voltage resistant electrolyte comprises a carbonate co-solvent, an electrolyte sodium salt, a carbonate electrolyte additive and a high-voltage resistant co-solvent; the carbonate co-solvent is propylene carbonate, the electrolyte sodium salt is sodium hexafluorophosphate (NaPF6), the carbonate electrolyte additive is fluoroethylene carbonate, and the high-voltage resistant co-solvent is ethyl methanesulfonate and cyclopentane sulfone; wherein the molar ratio of ethyl methanesulfonate, cyclopentane sulfone and propylene carbonate is 40:40:20, that is, the volume ratio of the high-voltage resistant co-solvent to the carbonate co-solvent is 80:20, the carbonate electrolyte additive accounts for 1% of the total volume of the high-voltage resistant co-solvent and the carbonate co-solvent, and the concentration of the electrolyte sodium salt is 1 mol / L.
[0043] The preparation method of the high-voltage electrolyte is as follows: ethyl methanesulfonate and propylene carbonate are mixed in a molar ratio, fluoroethylene carbonate is added, sodium hexafluorophosphate is added and the concentration is adjusted, and the electrolyte is obtained after being stirred evenly.
[0044] Example 5 A high-voltage resistant electrolyte, the other contents of which are the same as those of Example 1, except that the carbonate electrolyte additive accounts for 5% of the total volume of the high-voltage resistant co-solvent and the carbonate co-solvent.
[0045] Example 6 A high-voltage resistant electrolyte, the other contents of which are the same as those of Example 1, except that the volume ratio of the electrolyte to the carbonate co-solvent is 70:30.
[0046] Example 7 A high-voltage resistant electrolyte, other contents of which are the same as those of Example 1, except that the volume ratio of the high-voltage resistant co-solvent to the carbonate co-solvent is 50:50.
[0047] Example 8 A high-voltage resistant electrolyte, other contents of which are the same as those of Example 1, except that the volume ratio of the high-voltage resistant co-solvent to the carbonate co-solvent is 90:10.
[0048] Example 9 A high-voltage resistant electrolyte, other contents of which are the same as those of Example 1, except that the volume ratio of the high-voltage resistant co-solvent to the carbonate co-solvent is 10:90.
[0049] Example 10 A high-voltage resistant electrolyte, the other contents of which are the same as those of Example 1, except that fluoroethylene carbonate is replaced by difluoroethylene carbonate.
[0050] Embodiment 11 A high-voltage resistant electrolyte, other contents of which are the same as those of Example 1, except that the high-voltage resistant co-solvent is sulfolane.
[0051] Example 12 A high-voltage resistant electrolyte, other contents of which are the same as those of Example 1, except that the concentration of the electrolyte sodium salt is 2 mol / L.
[0052] Examples 13-24 A sodium ion battery, the assembly steps are as follows: layered oxide Na 0.67 Mn 0.8 Cu 0.2 O2 is used as the positive electrode, sodium metal electrode is used as the negative electrode, and the separator is a glass fiber separator (GF-D). The materials of Examples 1-12 are used as the electrolyte to assemble a button-type half-cell. 0.67 Mn 0.8 Cu 0.2 The steps for preparing the positive electrode sheet are as follows: 0.67 Mn 0.8 Cu 0.2 O2 powder, conductive agent acetylene black and adhesive polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 8:1:1, coated on aluminum foil, and vacuum dried.
[0053] Layered oxide Na 0.67 Mn 0.8 Cu 0.2The synthesis steps of O2 are as follows: Sodium acetate, manganese acetate, copper acetate, and citric acid are mixed in a molar ratio of 0.67:0.8:0.2:0.5, ultrapure water is added, and the mixture is placed in an evaporating dish and stirred at 100°C for evaporation. The evaporated solid is sintered at 400°C for 5h in a muffle furnace; then sintered at 850°C for 12h in an oxygen atmosphere in a tube furnace to obtain Na 0.67 Mn 0.8 Cu 0.2 O2.
[0054] Comparative Example 1 An electrolyte, other contents of which are the same as those of Example 1, except that a high-pressure resistant co-solvent is not included.
[0055] Comparative Example 2 An electrolyte, other contents of which are the same as those of Example 7, except that the high-pressure resistant co-solvent is replaced by ethylene carbonate.
[0056] Comparative Example 3 An electrolyte, other contents of which are the same as those of Comparative Example 2, except that NaPF6 is replaced by NaClO4.
[0057] Comparative Example 4 An electrolyte, other contents of which are the same as those of Example 5, except that a high-pressure resistant co-solvent is not included.
[0058] Comparative Examples 5-8 A sodium ion battery, the assembly steps are as follows: layered oxide Na 0.67 Mn 0.8 Cu 0.2 O2 is used as the positive electrode, sodium metal electrode is used as the negative electrode, and the separator is a glass fiber separator (GF-D). The materials of comparative examples 1-3 are used as electrolytes to assemble button-type half-cells. 0.67 Mn 0.8 Cu 0.2 The steps for preparing the positive electrode sheet are as follows: 0.67 Mn 0.8 Cu 0.2 O2 powder, conductive agent acetylene black and adhesive polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 8:1:1, coated on aluminum foil, and vacuum dried.
[0059] Test and Evaluation The half-cells of Example 13 and Comparative Example 5 were tested for cycle performance, that is, the half-cells assembled with the electrolytes of Example 1 and Comparative Example 1 were tested for cycle performance. The test results are as follows: Figure 1 As shown. Figure 1It can be seen that the half-cell assembled with the electrolyte of Comparative Example 1 decays significantly after 200 cycles, indicating that the positive electrode material Na 0.67 Mn 0.8 Cu 0.2 The crystal structure of O2 is gradually destroyed under high-voltage cycling, and its capacity retention rate is only 22.4% after 750 cycles at 1C, indicating that the service life of the half-cell assembled with the electrolyte of Comparative Example 1 is poor; while the half-cell assembled with the electrolyte of Example 1 has unstable specific capacity in the first 50 cycles, which can be considered as the process of forming a stable CEI film, and still maintains a capacity retention rate of 83.2% after 750 cycles, indicating that a dense CEI film has been formed on the surface of the positive electrode material, protecting the Na 0.67 Mn 0.8 Cu 0.2 O2 positive electrode material, indicating that the half-cell assembled with the electrolyte of Example 1 has a longer service life and better cycle performance.
[0060] The half-cells of Example 13 and Comparative Example 5 were subjected to ICP test after 400 cycles, i.e., the half-cells assembled with the electrolytes of Example 1 and Comparative Example 1 were subjected to ICP test after 400 cycles. The test results are as follows: Figure 2 As shown. Figure 2 It can be seen that the transition metal ion content in the diaphragm of the half-cell assembled with the electrolyte of Comparative Example 1 after 400 cycles is much higher than that of the diaphragm of the half-cell assembled with the electrolyte of Example 1 after 400 cycles, indicating that the CEI membrane formed by the half-cell assembled with the electrolyte of Comparative Example 1 cannot protect the positive electrode material, resulting in the dissolution of transition metal ions; while the transition metal ion content in the diaphragm of the half-cell assembled with the electrolyte of Example 1 after 400 cycles is low, indicating that Na 0.67 Mn 0.8 Cu 0.2 A dense CEI film has been formed on the surface of the O2 positive electrode material.
[0061] Figure 3 and Figure 4 The scanning electron microscope images of the positive electrode sheets of the half-cells of Example 13 and Comparative Example 5 after 400 cycles are shown. Figure 3 and Figure 4 The scanning electron microscope image of the positive electrode sheet of the half-cell assembled with the electrolyte of Example 1 and Comparative Example 1 after 400 cycles. Figure 3 and Figure 4 It can be seen from the comparison that after 400 cycles, the half-cell assembled with the electrolyte of Comparative Example 1 has Na 0.67 Mn 0.8 Cu 0.2 The O2 particles were broken; however, after 400 cycles, the Na 0.67 Mn0.8 Cu 0.2 The O2 crystal particle structure is still intact, indicating that the Na 0.67 Mn 0.8 Cu 0.2 The O2 particles have a stable structure during high-pressure cycling, thus exhibiting excellent cycling performance.
[0062] The sodium ion batteries prepared in Examples 13-24 and Comparative Examples 5-8 were subjected to constant current charge and discharge tests (test voltage range 2-4.5 V), thereby obtaining the long-cycle capacity retention rate (750 cycles). The test results are shown in Table 1.
[0063] Table 1 Cycle performance test results Electrolyte Cut-off voltage Capacity retention after 400 cycles Capacity retention after 750 cycles Embodiment 13 4.5V 95.51% 83.20% Embodiment 14 4.5V 65.59% / Embodiment 15 4.5V 81.72% 78.76% Example 16 4.5V 82.34% 80.61% Embodiment 17 4.5V 58.51% / Embodiment 18 4.5V 61% / Embodiment 19 4.5V 63.28% / Embodiment 20 4.5V 50.13% / Embodiment 21 4.5V 51.15% / Embodiment 22 4.5V 65.64% / Embodiment 23 4.5V 63.66% / Embodiment 24 4.5V 61.95% / Comparative Example 5 4.5V 57.07% 22.40% Comparative Example 6 4.5V 36% / Comparative Example 7 4.5V 26.9% / Comparative Example 8 4.5V 61.15% 24.21% Note: “ / ” in Table 1 means that the experimental test was not conducted.
[0064] The above results show that the addition of sulfonate co-solvents and / or sulfone co-solvents can significantly improve the cycle performance of the battery; at the same time, compared with the use of difluoroethylene carbonate as an additive, the use of fluoroethylene carbonate is more conducive to improving the cycle performance of the battery and is conducive to reducing the amount of carbonate additives; it also shows that sodium salts, eutectic solvents and additives can further improve the cycle performance of the battery within a suitable range.
[0065] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A high voltage resistant electrolyte, characterized in that: The invention comprises a carbonate co-solvent, an electrolyte sodium salt, a carbonate electrolyte additive and a high-voltage co-solvent, wherein the high-voltage co-solvent is a sulfonate co-solvent and / or a sulfone co-solvent.
2. The high voltage resistant electrolyte according to claim 1, characterized in that: The sulfonate co-solvent includes at least one of ethyl methanesulfonate, ethyl benzenesulfonate, and ethyl p-toluenesulfonate.
3. The high voltage resistant electrolyte according to claim 1, characterized in that: The sulfone co-solvent includes at least one of sulfolane and ethyl methyl sulfone.
4. The high voltage resistant electrolyte according to claim 1, characterized in that: The carbonate electrolyte additive includes at least one of fluoroethylene carbonate, difluoroethylene carbonate and vinylene carbonate.
5. The high voltage resistant electrolyte according to claim 1, characterized in that: The carbonate co-solvent includes at least one of ethylene carbonate and propylene carbonate; the electrolyte sodium salt includes at least one of sodium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate and sodium bis(fluorosulfonyl)imide.
6. The high voltage resistant electrolyte according to claim 1, characterized in that: The volume ratio of the high pressure resistant co-solvent to the carbonate co-solvent is (25-80): (20-75).
7. The high voltage resistant electrolyte according to claim 1, characterized in that: The carbonate electrolyte additive accounts for 1-5% of the total volume of the high-voltage co-solvent and the carbonate co-solvent.
8. The high voltage resistant electrolyte according to claim 1, characterized in that: The concentration of the electrolyte sodium salt in the high-voltage resistant electrolyte is 0.8-2 mol / L.
9. A sodium ion battery, characterized in that: The invention comprises a high voltage resistant electrolyte as described in any one of claims 1 to 8, a layered oxide positive electrode material, a negative electrode material and a separator.
10. Use of the sodium ion battery according to claim 9 at 2-4.5V.
